Optimal primary wound closure methods after thyroid and parathyroid surgery: network meta-analysis of randomized clinical trials. Issue 1 (23rd February 2023) - Davey, Matthew G; Browne, Ferdia; Davey, Martin S; Walsh, Stewart R; Kerin, Michael J; Lowery, Aoife J
Abstract: Background: At present, there is no consensus on optimal neck wound closure methods after thyroid and parathyroid surgery. The aim of this study was to perform a systematic review and network meta-analysis of RCTs evaluating the optimal neck closure method after thyroid and parathyroid surgery. Methods: A frequentist random-effects network meta-analysis was performed for RCTs comparing at least two closure methods according to PRISMA-network meta-analysis guidelines. Analysis was performed using R packages and Shiny. Results: Eighteen RCTs evaluating six closure methods (that is adhesive (28.5 per cent, 404 patients), absorbable subcuticular suture (18.1 per cent, 257 patients), non-absorbable subcuticular suture (16.8 per cent, 238 patients), staples (26.3 per cent, 372 patients), steristrips (8.1 per cent, 115 patients), and conventional suture (2.1 per cent, 30 patients)) in 1416 patients were included. At network meta-analysis, there was no difference in complication, infection, dehiscence, or haematoma rates irrespective of closure method used. Staples reduced closure duration versus absorbable subcuticular suture (mean difference (MD) 8.50, 95 per cent c.i. 6.90 to 10.10) and non-absorbable subcuticular suture (MD 0.30, 95 per cent c.i. 0.23 to 0.37), whereas adhesives (MD −1.05, 95 per cent c.i. −1.31 to −0.79) reduced closure time relative to staples. Cosmesis was improved after non-absorbable subcuticular suture (odds ratio (OR) 3.41, 95 per cent c.i. 1.66 to 7.00) relative to staples. Staples reduced patient satisfaction (OR 0.04, 95 per cent c.i. 0.00 to 0.33) and ability to shower (OR 0.04, 95 per cent c.i. 0.00 to 0.33) relative to adhesives. Conclusion: Despite staples decreasing closure times, this advantage is offset by reduced patient satisfaction, ability to shower, and cosmesis compared with patients with wounds closed using adhesives, absorbable subcuticular suture, and non-absorbable subcuticular suture. Therefore, these closure methods are favourable for closing neck wounds due to more acceptable patient-reported outcomes, without compromising the safety of the procedure. Abstract : This is a systematic review and network meta-analysis evaluating the utility of varying wound closure methods after thyroid and parathyroid surgery. The results illustrate that subcuticular sutures are favourable for closing neck wounds due to more acceptable patient-reported outcomes compared with other closure methods, without compromising safe closure.